Hooliganism in the shadow of the 9/11 terrorist attack and the Tsunami: do police reduce group violence? - Panu Poutvaara; Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper isolates the causal effect of policing on group violence, using unique panel data on self-reported crime by soccer and ice hockey hooligans. The problem of reverse causality from violence to policing is solved by two drastic reallocations of the Stockholm Supporter Police unit to other activities following the 9/11 terrorist attack in September 2001 and the Tsunami catastrophe in December 2004. Difference-in-difference analysis reveals that Stockholm-related hooligan violence increased dramatically during these periods.
Keywords: K10; K42; 330; Gewalt; Soziale Gruppe; Sport; Kriminalpolitik; Schweden